BIM benefits and its influence on the BIM implementation in Malaysia - Al-Ashmori, Y.Y. (Ain Shams University, 2020)
Building Information Modelling (BIM) implementation is considered a daunting reality because majority of the construction players don't know the potential benefits of the technology. Awareness of BIM benefits and its implementation could significantly increase project productivity and performance. This study is aimed to determine the influence of BIM benefits from the Malaysian construction stakeholdersâ perception towards its implementation. The study was carried out using survey questionnaire. Out of 590 questionnaires 268 were collected that represent a sample size of 346. Results revealed that most of the construction companies lack of awareness about BIM technology. The statistical analysis showed that productivity, time, cost, clashes, and communication are the most essential BIM benefits that concerned the participants. The driving factors of implementation, on the other hand, were identified as Trust, respect, commitment, early involvement, and knowledge. It is also found that there is a significant relationship between BIM benefits and its implementation. Â© 2020 THE AUTHORS